Variants in PRKAR1B cause a neurodevelopmental disorder with autism spectrum disorder, apraxia, and insensitivity to pain - Marbach, Felix; Stoyanov, Georgi; Erger, Florian; Stratakis, Constantine A.; Settas, Nikolaos; London, Edra; Rosenfeld, Jill A.; Torti, Erin; Haldeman-Englert, Chad; Sklirou, Evgenia; Kessler, Elena; Ceulemans, Sophia; et al. (Genetics in medicine, 2021)
We characterize the clinical and molecular phenotypes of six unrelated individuals with intellectual disability and autism spectrum disorder who carry heterozygous missense variants of the PRKAR1B gene, which encodes the R1β subunit of the cyclic AMP-dependent protein kinase A (PKA).
Gesehen am 20.04.2021